Results of the scientific dialogue: Problems of psychological services development and functioning in the system of professional education - Milena A. Klenova; Kseniya A. Yakovleva; Alina K. Lyubakova (Saratov State University, 2022)
The article presents the results of the interregional round table with international participants "Problems of Psychological Services Development and Functioning in the System of Professional Education". The round table was organized by Saratov State Law Academy, the Center of Psychological Support of Saratov State Law Academy, on the one hand, and the Institute of Youth, the Institute of Psychoanalysis and the Philosophy Department of the State Academic University for the Humanities, on the other hand. The paper shows the results of the round table meeting and master classes. It indicates the problems of the psychological services formation and their functioning in the system of professional education. Moreover, the article presents the urgent tasks of psychological services in the system of professional education. The results of the round table are summarized.